Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

2[6+4{m-6(7-n-p)+q}]
Algebraic expression​


Sagot :

Answer:

2(6+4(m−6(7−n−p)+q))

=(2)(6+4(m−6(7−n−p)+q))

=(2)(6)+(2)(4(m−6(7−n−p)+q))

=12+8m+48n+48p+8q−336

Answer =8m+48n+48p+8q−324

2(6+4(m−6(7−n−p)+q))

=(2)(6+4(m−6(7−n−p)+q))

=(2)(6)+(2)(4(m−6(7−n−p)+q))

=12+8m+48n+48p+8q−336

Answer =8m+48n+48p+8q−324